2002
DOI: 10.1002/aqc.530
|View full text |Cite
|
Sign up to set email alerts
|

Supporting complex decisions for sustainable river management in England and Wales

Abstract: ABSTRACT1. Sustainable river management demands a strategic approach that renders even routine decisions highly complex if they are to be consistent, transparent and accountable. Under these circumstances, there is an increasing need for decision-support systems, although carefully structured guidelines and statements of best practice will continue to play a major supporting role.2. This support is likely to be particularly important in wide-ranging contexts, from routine decisions in determining land drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…The need for decision making and communication tools is a consequence of: (i) the diversity of stakeholders involved in river management; (ii) acknowledging the complexity and inherent uncertainty in managing river systems; and (iii) the concomitant capacity for conflicts of interest (Clark and Richards, 2002). Potential conflicts occur frequently, such as the desire to increase water abstraction for drinking and agriculture, compared with the desire to minimize human impacts.…”
Section: Decision Making and Communication Toolsmentioning
confidence: 99%
“…The need for decision making and communication tools is a consequence of: (i) the diversity of stakeholders involved in river management; (ii) acknowledging the complexity and inherent uncertainty in managing river systems; and (iii) the concomitant capacity for conflicts of interest (Clark and Richards, 2002). Potential conflicts occur frequently, such as the desire to increase water abstraction for drinking and agriculture, compared with the desire to minimize human impacts.…”
Section: Decision Making and Communication Toolsmentioning
confidence: 99%
“…This might in the future include information from other scientific disciplines, the results of new research, and the views of stakeholders (for example, fishing clubs might score and weight attributes such as pool-riffle sequences more highly than might flood risk managers). Clark and Richards (2002) argue that inevitably MCA-based decision support systems cannot make decisions but exist to help inform them. Central to this is to ensure that the information is presented in a format that is not overly-technical.…”
Section: Discussionmentioning
confidence: 99%
“…These are given a score according to their significance to the definition of reference condition. These values could be crisp boundaries, but might equally be represented by fuzzy boundaries where there is uncertainty over the precise score (Klir and Yuan, 1995;Clark and Richards, 2002). As an example, in defining an upstream barrier to sediment transport, a small weir which controls coarse but not fine sediment movement might receive a lower score than a dam, which traps all sediment in a large upstream reservoir.…”
Section: Multi-criteria Assessmentmentioning
confidence: 98%
“…, which can be traded for gains in the other essential characteristics of models.' Others have suggested that recognising that not all uncertainty is bad will be increasingly important to decision makers who are forced to make decisions in the face of uncertainty (Clark and Richards, 2002;Pollack, 2003). Especially in long term policy analysis (the next 20-100 years) decision makers are faced with what Lempert et al (2003) referred to as 'deep uncertainty'.…”
Section: Embrace Uncertaintymentioning
confidence: 99%